Teachers’ Lived Experiences of Family Factors Influencing the Formation of Social Identity among Secondary School Students in Iraq - Abdullah Al Sbaar, Atheer Fadhil; ShahTalebi, Badri; Shanta Jaber, Jalal; Faeghi, Sahar (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to identify teachers' lived experiences regarding family factors influencing the formation of social identity in secondary school students in Iraq.Methods and Materials: In the first part of the research, a phenomenological approach using Colaizzi’s seven-step method was applied. The research environment for the first phase consisted of social studies teachers, who were selected through purposive sampling based on criteria. The instrument used was semi-structured in-depth interviews. The interviews continued until theoretical saturation was reached, with a total of 26 participants. Initial coding led to the identification of 28 primary concept codes, categorized under demographic factors, cognitive knowledge of family, and behavioral knowledge of family. In the second phase of the study, to validate the conceptual model from the qualitative section, a descriptive correlational research method was employed. The statistical population for this phase comprised all social studies teachers at the secondary school level employed in public education in Iraq, totaling 1,200 teachers. From this group, 290 teachers were selected using the table of Krejcie and Morgan (1970) and a convenience sampling method. The instrument used in this phase was a researcher-made questionnaire derived from the qualitative section of the study, consisting of 28 items on a five-point Likert scale.Findings: The content validity of the instrument was confirmed by several experts, and its face validity was confirmed by a number of respondents. The reliability of the questionnaire was assessed using Cronbach’s alpha coefficient, which yielded a value of 0.990. The validation of the proposed model and data analysis using structural equation modeling in Amos and SPSS software showed that the model of family factors influencing the formation of social identity in secondary school students fit well.Conclusion: In conclusion, family factors play a pivotal role in shaping adolescents' social identity, with emotional support, autonomy, and parenting style significantly influencing their identity development and overall social health.